Effect of the Earth's inner structure on the gravity in definitions of height systems. Issue 1 (20th January 2017) - Tenzer, Robert; Foroughi, Ismael; Pitoňák, Martin; Šprlák, Michal
Abstract: In context of the vertical datum unification, the geoid-to-quasi-geoid separation has been of significant interest in recent years, because most of existing local vertical datums are realized in the system of either normal or orthometric heights. Nevertheless, the normal–orthometric heights are still used in many other countries where the normal gravity values along leveling lines were adopted instead of the observed gravity. Whereas the conversion between the orthometric and normal heights is defined by means of the mean gravity disturbances (i.e. differences between the mean values of the actual and normal gravity) along the plumbline within the topography, differences between the normal and normal–orthometric heights can be described by means of the surface gravity disturbances. Since the normal gravity field does not reflect the topographic masses and actual mass density distribution inside the Earth, the definition of gravity represents a principal aspect for a realization of particular vertical datum. To address this issue in this study, we investigate effects of the Earth's inner density structure on the surface and mean gravity disturbances, and discuss their impact on the vertical datum realization. These two gravity field quantities are computed globally with a spectral resolution complete to a spherical harmonic degree 2160 using the global gravity, terrain, ice-thickness, inland bathymetry and crustal structure models. Our results reveal that both, the surface and mean gravity disturbances mostly comprise the gravitational signal of topography and masses distributed below the geoid surface. Moreover, in polar areas, a significant contribution comes from large glaciers. In contrast, the contributions of anomalous density distribution within the topography attributed to major lakes, sediments and bedrock density variations are much less pronounced. We also demonstrate that the mean gravity disturbances within the topography are significantly modified compared to the corresponding surface values mainly due to topographic elevation and terrain geometry as well as the presence of large glaciers in polar regions. Changes of the vertical gravity gradient within the topography attributed to the masses distributed below the geoid (dominated mainly by the isostatic signature and the long-wavelength gravitational signature of deep mantle density heterogeneities) are, on the other hand, relatively small. Despite differences between the normal and normal–orthometric heights could directly be assessed from the surface gravity disturbances only when taken along leveling lines with information about the spirit leveling height differences, our results indicate that differences between these two height systems can be significant.